Endometrioid carcinoma arising from diaphragmatic endometriosis treated with laparoscopy: A case report. Issue 5 (5th February 2018) - Okimura, Hiroyuki; Tatsumi, Hiroshi; Ito, Fumitake; Yamashita, Suguru; Kokabu, Tetsuya; Kitawaki, Jo
Abstract: Malignant transformation of diaphragmatic endometriosis is rare. We present a case of endometrioid carcinoma arising from diaphragmatic endometriosis treated with laparoscopy. A 59‐year‐old primigravida woman who had undergone abdominal hysterectomy for adenomyosis at the age of 47 years was referred to our hospital for investigation of a tumor on the surface of the liver. An integrated positron emission tomography‐computed tomography scan revealed a 3‐cm nodule on the surface of the liver with abnormal fluorine‐18‐deoxyglucose accumulation. Partial resection of the diaphragm and liver was performed. Histopathological examination revealed an endometrioid carcinoma arising from diaphragmatic endometriosis. We additionally performed laparoscopic bilateral salpingo‐oophorectomy and partial omentectomy. The resected tissues revealed no malignancy. Adjuvant chemotherapy with paclitaxel and carboplatin was administered. In cases of diaphragmatic tumors, endometriosis and its associated malignancies should be considered. Laparoscopic surgery is effective in patients with such conditions.